2017
DOI: 10.1111/bcp.13177
|View full text |Cite
|
Sign up to set email alerts
|

Venlafaxine and oxycodone have different effects on spinal and supraspinal activity in man: a somatosensory evoked potential study

Abstract: AIMSOpioids and antidepressants that inhibit serotonin and norepinephrine reuptake (SNRI) are recognized as analgesics to treat severe and moderate pain, but their mechanisms of action in humans remain unclear. The present study aimed to explore how oxycodone (an opioid) and venlafaxine (an SNRI) modulate spinal and supraspinal sensory processing. METHODSTwenty volunteers were included in a randomized, double-blinded, three-way (placebo, oxycodone, venlafaxine), crossover study. Spinal and full scalp cortical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…We also found venlafaxine to reduce functional connectivity to parietal regions. Additionally, using the same cohort of healthy volunteers as in the present study, in our previous EEG study involving spinal and cortical evoked potentials, we observed a decrease in latencies induced by venlafaxine treatment, and in an EEG study involving tonic pain, we observed a decrease in alpha activity induced by venlafaxine treatment, which was correlated to decrease in pain scores . The observed changes in the surface EEG could be related to changes in functional connectivity observed in our present MRI study.…”
Section: Discussionsupporting
confidence: 80%
“…We also found venlafaxine to reduce functional connectivity to parietal regions. Additionally, using the same cohort of healthy volunteers as in the present study, in our previous EEG study involving spinal and cortical evoked potentials, we observed a decrease in latencies induced by venlafaxine treatment, and in an EEG study involving tonic pain, we observed a decrease in alpha activity induced by venlafaxine treatment, which was correlated to decrease in pain scores . The observed changes in the surface EEG could be related to changes in functional connectivity observed in our present MRI study.…”
Section: Discussionsupporting
confidence: 80%
“…Early cortical activation was analysed at the negative potential (N20) and the positive potential (P22), at the centro‐parietal CP5 electrode contralateral to the stimulation, and the peak‐to‐peak amplitude was used. In a similar way the latencies and amplitude of the subcortical response (N14‐P18) was analysed at the occipital midline electrode (Oz), and late cortical response (N60‐P80) was assessed at the central midline electrode C1 …”
Section: Methodsmentioning
confidence: 99%
“…In this regard, there are several potential confounders for the neurophysiological testing (eg, NWR) including diabetes and analgesics that may influence our results such as recently shown by our group. 28,49,50 We did, however, take this partly into account since we stratified for opioid use in our analysis. Due to the relatively small sample size, the validity of the correlation analyses may be limited, and there was an overall increased risk of type 2 errors.…”
Section: Limitationsmentioning
confidence: 99%